Implementation of Artificial Mangrove Roots FADS in Preventing Abrasion - Pujianiki, Ni Nyoman; Thanawatth, Sattabongkot; Warit, Charoenlerkthawin; Butsawan, Bidorn; Haryo, Dwito Armono; Denny, Nugroho Sugianto (INTI International University, 2025)
FADS (Flotilla Abrasion Defense System) is coastal protection system designed to imitate mangrove roots, which serve to protect beaches and help retain sediment. As we know, it takes a long time for natural mangrove roots to grow strong and large. An innovation has been developed to create artificial mangrove roots, providing immediate access to the protective benefits of mangrove roots. FADS are made from environmentally friendly materials that are durable for up to 12 years. Testing and implementation have been carried out on sandy and muddy beaches in Thailand, and the results show that FADS perform effectively.